2011
DOI: 10.1308/147870811x580442
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell tumour: late recurrence after 43 years

Abstract: We report the late relapse of a patient following 43 years of surveillance of a germ cell tumour, thought to be a pure seminoma, having undergone yolk sac differentiation. The longest previous recorded time to relapse was 32 years (malignant teratoma with adenocarcinoma de-differentiation).(1) This case report demonstrates a late relapse of a testicular germ cell tumour is possible whatever the initial stage. European Association of Urology guidelines state close and active follow-up is mandatory for at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…To our knowledge, only two later cases have been reported 9,10 and only 1% of patients will relapse three or more years postorchiectomy. 3 This case and other rare late relapse cases raise the question of whether lifetime imaging surveillance should be performed for CSI NSGCT patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…To our knowledge, only two later cases have been reported 9,10 and only 1% of patients will relapse three or more years postorchiectomy. 3 This case and other rare late relapse cases raise the question of whether lifetime imaging surveillance should be performed for CSI NSGCT patients.…”
Section: Discussionmentioning
confidence: 84%
“…1 Additionally, a literature search found an additional two cases of very late relapse (32 and 43 years). 9,10 The nature of late relapse CSI NSGCT biology means that patients who relapse are commonly symptomatic and present most often with abdominal pain. 9,11,12 Case report We present a rare case of a 28-year post-orchiectomy late relapse in a 50-year-old male who underwent left radical orchiectomy in 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the report by Oldenburg et al [7], the incidence rates were 1.4 and 3.2% in pure seminoma and nonseminoma patients, respectively. In addition, Mukhtar et al [11] and Pavic et al [12] reported cases of late recurrence after 43 years and 32 years, respectively. Therefore, clinicians should be aware of the possibility of late relapse after successful treatment in patients with stage I testicular germ cell tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients with stage I testicular germ cell tumors show relapse within 2–3 years after orchiectomy [2, 3, 4, 5, 6]. Although late relapse of testicular seminoma has been reported in the literature [7, 8, 9, 10, 11, 12], it is extremely rare. In particular, relapse over 10 years after treatment is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…Two case reports are similar to this case, Arafat et al describe a case involving a patient with stage I NSGCT who relapsed with a retroperitoneal mass after 27 years [ 19 ] and Lattouf et al a case of stage I NSCGT who presented with a seminal vesicle relapse after 20 years [ 20 ]. For seminoma combined with yolk-sac tumour, late relapse after 43 years of surveillance has been described [ 21 ]. Notably, the published literature on case series in seminoma suggests that late relapse beyond 10 years is more common than for non-seminomas [ 7 , 8 , 22 ].…”
Section: Discussionmentioning
confidence: 99%